KAJIAN PEMULSAAN DALAM MEMPENGARUHI SUHU TANAH, SIFAT TANAH, DAN PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin Benth) - Nasruddin Nasruddin; Hamidah Hanum (Jurnal Floratek, 2015)
This study was aimed at assessing effects of mulch on soil temperature, physical properties of soil, and growth of patchouli. The experiment was conducted in Village ReuleutTimu, Sub District MuaraBatu, District Aceh Utara, from June to September 2013. The experiment was arranged in a randomized block design with three replicates. Types of mulching consisted of five levels i.e. without mulching, rice straw spread 10 tons ha-1, rice straw mulch spread 5 ton ha-1 + embedded 5 ton ha-1, sawdust spread 10 tons ha-1, sawdust spread 5 ton ha-1 + embedded 5 ton ha-1.The variables observed were soil temperature, bulk density, C-organic, N-total, C/N ratio, porosity of the soil, plant height, number of branches, leaf area, and dry weight of plants. Results showed that mulching resulted in lowering temperature, value of bulkdensity, and ratio of C/N soil, andincreasing levels of N-total, and improving soil porosity.  Mulching also affected plant height, number of branches, leaf area, and plant dry weight. Rice straw provided lower degree of soil temperatures than sawdust, but did not provide better of plant height, number of leaves, leaf area and dry weight of plants. Spread rice straw provided lower soil temperature and better leaf area at 60 day after planting but lesser dry weight at 75 day after plantingthan spread+embedded rice straw.